904. RHODODENDRON LEPTOCLADON: Ericaceae. (9th April 2019) - Rushforth, Keith; Huong, Nguyen Thi Thanh
Summary: Rhododendron leptocladon Dop is illustrated. Further information on this little‐known species is given, and its status within section Rhododendron Subsection Maddenia is discussed.